Sodobna sintezna zdravila za zdravljenje astme - Kikelj, Danijel (Farmacevtski vestnik, 2013)
Asthma is a chronic airway disorder characterized by airflow obstruction and an underlying inflammation. Asthma symptoms are caused by bronchoconstriction and inflammation, and therapeutical approached are directed at both of these patophysiological problems. The paper brings an overview of modern synthetic drugs for treatment and management of asthma, including bronchoselective adrenergic beta2 agonists, anticholinegics, glucocorticoids, leukotriene biosynthesis inhibitors, leukotriene receptor antagonists and phosphodiesterase inhibitors.
Keywords: asthma; astma; drug; zdravila